PENGARUH SISTEM INFORMASI AKUNTANSI DAN KETEPATAN PEMBAYARAN PIUTANG TERHADAP PENGENDALIAN INTERNAL PENJUALAN (Studi Pada Divisi Usaha Bharakerta Inkoppol) - Pujiati, Herni (AGUSPATI Research Institute, 2021)
The purpose of this research is to find out the influence of accounting information system and payment punctuality of account receivable to the sales internal control at Divisi Usaha Bharakerta Inkoppol. The method of research is qualitative method. The sample collection technique is conducted by performing non- probability sampling and saturated sampling technique approach. The primary data is obtained by distributing questionnaires. This research uses several test which are partial test (t-test) and multiple linear regression. Accounting information system (X1) has a positive and significant effect on internal sales at the Bharakerta Inkoppol Business Division. Implementing this by increasing the application of accounting information systems will improve internal sales control in the Bharakerta Inkoppol Business Division. The results of the accurate payment of receivables (X2) have a positive and significant impact on sales internal control (Y) in the Bharakerta Inkoppol Business Division. This means that the better application of payment accuracy will improve the internal sales control of the Bharakerta Inkoppol Business Division. Accounting information system (X1) and the results of the accuracy of payment of accounts receivable (X2)) have a positive and significant effect on internal sales control (Y) at the Bharakerta Inkoppol Business Division. This indicates that the accounting information system and the accuracy of payment of accounts receivable are components in creating good and clean internal control